2017
DOI: 10.1553/eco.mont-9-sis66
|View full text |Cite
|
Sign up to set email alerts
|

A demographic perspective on the spatial behaviour of hikers in mountain areas: the example of Berchtesgaden

Abstract: In Germany, as in many Western societies, demographic change will lead to a higher number of senior visitors to natural recreational areas and national parks. Given the high physiological requirements of many outdoor recreation activities, especially in mountain areas, it seems likely that demographic change will affect the spatial behaviour of national park visitors, which may pose a challenge to the management of these areas. With the help of GPS tracking and a standardized questionnaire (n=481), this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our study didn't confirmed relation of different demographic data (Kruger, Viljoen, Saayman 2017), gender and age (Petrovic, Tomicevic-Dubljevic, Stavretovic 2016) or group size (Meijles et al 2014) to the use of the area. Activity type and age could affect the spatial behavior of park visitors through the high physiological requirements of many outdoor recreational activities, especially in mountain areas (Schamel 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study didn't confirmed relation of different demographic data (Kruger, Viljoen, Saayman 2017), gender and age (Petrovic, Tomicevic-Dubljevic, Stavretovic 2016) or group size (Meijles et al 2014) to the use of the area. Activity type and age could affect the spatial behavior of park visitors through the high physiological requirements of many outdoor recreational activities, especially in mountain areas (Schamel 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the struggle to improve the research process, authors are striving to validate new methods, mainly to ease the process and reduce or overcome the limitations of traditional instruments (time-consuming, expensive, incomplete information, human error). Some authors choose to analyse information already available on social media platforms to understand consumer behaviour [32,49,53,71], while others take a different approach, analysing GPS/PPGIS tracks to study travel patterns [55,63,65,73,80,82,90,92,94,104], and a few authors, such as Barros et al [58], use both methods.…”
Section: No Of Published Papersmentioning
confidence: 99%